2021
DOI: 10.3390/pathogens10060780
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis E Virus Infection among Laboratory Rabbits in China

Abstract: Hepatitis E virus (HEV) is zoonotic and the leading cause of acute viral hepatitis worldwide. Rabbit HEV can infect humans and is prevalent globally. It is reported that laboratory rabbits are also naturally infected with HEV. Therefore, it is important to investigate in a large scale the prevalence of HEV in laboratory rabbits. Serum samples were collected from 649 laboratory rabbits of 13 different commercial vendors in Beijing, China, from 2017 to 2019, and anti-HEV and HEV antigen (Ag) were tested. Fecal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Several studies reported HEV-3ra worldwide in wild, laboratory and domestic rabbits with variable prevalence: 16.4% in the United States [20], 3.5% in Australia [21], 12.0% from laboratory rabbits [22] and 11.4% from farmed rabbits in China [23], and 6.4% in farmed rabbits from Korea [24]. Overall, the prevalence is variable and significantly lower than that observed in pigs [4].…”
Section: Introductionmentioning
confidence: 97%
“…Several studies reported HEV-3ra worldwide in wild, laboratory and domestic rabbits with variable prevalence: 16.4% in the United States [20], 3.5% in Australia [21], 12.0% from laboratory rabbits [22] and 11.4% from farmed rabbits in China [23], and 6.4% in farmed rabbits from Korea [24]. Overall, the prevalence is variable and significantly lower than that observed in pigs [4].…”
Section: Introductionmentioning
confidence: 97%